Regeringsautonomi og delegeringstab i dansk EU-politik: Et principal-agent teoretisk perspektiv - Pedersen, Rasmus Bruun (Politik, 2010)
Where do states’ positions on EU-integration come from? Despite a large number of studies we simply do not know which factors determine states’ positions in specific cases and why. This article analyses position making between ‘governments’ and ‘parliaments’ during the Maastricht Treaty negotiations. Furthermore, an analysis of the role of information asymmetries as intermediating factors in generating ‘influence on position’ will be carried out. The question asked is: Do governments enjoy relative autonomy vis-à-vis the Folketing that enables them to develop ‘positions’ they feel are in ‘the national interest’ or is Parliament able to control government behavior? The conclusions indicate that Parliaments control governmental positions, but also that governments, are able to exploit the negotiations to pursue certain ‘policy drifts’. The research design used is an in-dept single case study that analyses the level of inFluence on a multitude of different issues varied over the conflict level between the actors.